Relationship between energy availability, energy conservation and cognitive restraint with performance measures in male endurance athletes - Jurov, I.; Keay, N.; Hadžic, V.; Spudic, D.; Rauter, S. (Journal of the International Society of Sports Nutrition, 2021)
Background: Low energy availability in male athletes has gained a lot of attention in recent years, but direct evidence of its effects on health and performance is lacking. The aim of this research was to objectively measure energy availability (EA) in healthy male endurance athletes without pre-existing relative energy deficiency signs during pre-race season. Methods: Twelve trained endurance athletes (performance level 3, 4, and 5) participated in the cross-sectional controlled laboratory study. Fat-free mass, exercise energy expenditure, and energy intake were measured to calculate EA. Resting energy expenditure was measured and estimated to assess energy conservation. Three specific performance tests were used to assess endurance, agility, and explosive strength performance. For psychological evaluation, the Three Factor Eating Questionnaire and a short Well-being questionnaire were completed. Results: Mean EA was 29.5 kcal/kg FFM/day. The majority (66.6%) had EA under the threshold for low EA in females. Critical cognitive restraint (=13) was reported by 75% of participants. There were no differences in performance, blood values, or psychological evaluation when subjects were divided into two groups divided by EA = 30 kcal/kg FFM/day. Cognitive restraint was negatively associated with measured resting energy expenditure and energy conservation (r = -.578, p = .025 and r = -.549, p = .032, respectively). Conclusions: The mean EA measured in this study supports the theory that the threshold for low EA in endurance male athletes might be under the threshold for females. In addition, we confirmed cognitive restraint could be useful for early detection of energy conservation. The high cognitive restraint as measured in our sample stressed the need of eating behavior screening in endurance athletes in order to reduce risk of any disordered eating patterns.